The Passage of Chaperonins to Extracellular Locations in Legionella pneumophila Requires a Functional Dot/Icm System - Peter Robertson; David S. Allan; Rafael A. Garduño (Biomolecules)
HtpB, the chaperonin of the bacterial pathogen L. pneumophila, is found in extracellular locations, even the cytoplasm of host cells. Although chaperonins have an essential cytoplasmic function in protein folding, HtpB exits the cytoplasm to perform extracellular virulence-related functions that support L. pneumophila’s lifestyle. The mechanism by which HtpB reaches extracellular locations is not currently understood. To address this experimental gap, immunoelectron microscopy, trypsin-accessibility assays, and cell fractionation were used to localize HtpB in various L. pneumophila secretion mutants. Dot/Icm type IV secretion mutants displayed less surface-exposed HtpB and more periplasmic HtpB than parent strains. The analysis of periplasmic extracts and outer membrane vesicles of these mutants, where HtpB co-localized with bona fide periplasmic proteins, confirmed the elevated levels of periplasmic HtpB. Genetic complementation of the mutants recovered parent strain levels of surface-exposed and periplasmic HtpB. The export of GSK-tagged HtpB into the cytoplasm of infected cells was also Dot/Icm-dependent. The translocating role of the Dot/Icm system was not specific for HtpB because GroEL, the chaperonin of Escherichia coli, was found at the cell surface and accumulated in the periplasm of Dot mutants when expressed in L. pneumophila. These findings establish that a functional Dot/Icm system is required for HtpB to reach extracellular locations, but the mechanism by which cytoplasmic HtpB reaches the periplasm remains partially unidentified.